An easy and unique design strategy for insoluble humic acid/cellulose nanocomposite beads with highly enhanced adsorption performance of low concentration ciprofloxacin in water. (April 2020) - Wang, Langrun; Yang, Cong; Lu, Ang; Liu, Shilin; Pei, Ying; Luo, Xiaogang
Graphical abstract: Highlights: Homogeneous insoluble humic acid/cellulose nanocomposite beads (IHA@CB) were designed. Adsorption performance of IHA@CB was enhanced by HA in the cellulose matrix and IHA. Porous structured IHA@CB had high ciprofloxacin adsorption capacity of 10.87 mg g −1. Cation exchange was the dominant mechanism of the adsorption process. Abstract: In this work, two plant wastes were reused to fabricate the homogeneous 3D micro-nano porous structured humic acid/cellulose nanocomposite beads (IHA@CB) embedded with insoluble humic acid (IHA) particles. The subtle synthesis method attributed to the homogenous distribution of IHA particles in the cellulose matrix and improved the adsorption performance of IHA@CB for low concentration ciprofloxacin in water. Physical and chemical properties of the beads were characterized by SEM, EDX, XRD, FTIR, and the adsorption process of ciprofloxacin was studied by isotherm, kinetic and dynamic adsorption experiments. The maximum adsorption capacity of IHA@CB on CPX reached 10.87 mg g −1 under 318 K. The dynamic experiments were conducted by adjusting bed height, flow rate, initial concentration and pH values, and the regeneration experiments proved the adsorbent exhibited good repeatability. The adsorption mechanism was revealed that CPX was adsorbed by IHA@CB mainly through cation exchange.